Prognostic factors of metastatic neuroendocrine carcinoma under first-line treatment with platinum etoposide with a focus on NEC score and Rb expression: Results from the multicentre RBNEC study of the Groupe d'Etude des Tumeurs Endocrines (GTE) and the ENDOCAN-RENATEN network. (July 2021) - Hadoux, Julien; Kanaan, Christina; Durand, Alice; Hescot, Ségolène; Hautefeuille, Vincent; Cadiot, Guillaume; Tauveron, Igor; Laboureau, Sandrine; Do Cao, Christine; Walter, Thomas; Petorin, Caroline; Blanchet, Odile; et al.
Abstract: Introduction and aim: : Neuroendocrine carcinomas (NECs) are aggressive malignant diseases. Platinum-etoposide (PE) combination is the standard first-line treatment, whatever the primary location. The NEC score and also retinoblastoma protein (Rb) status have been suggested to be predictive/prognostic factors in NEC. The primary objective of our multicentric retrospective study was to evaluate the prognostic relevance of the NEC score and Rb status, assessed by immunohistochemistry in PE-treated patients with metastatic NEC. Methods: Seven centres participated. The inclusion criteria were NEC, whatever the primary site, metastatic stage, first-line treatment with PE and tissue samples available. Rb status was determined centrally. Results: We report multicentric data from 185 metastatic patients (37% women, median age 63). There were 108 small-cell NECs (SCNECs, 58.4%), 50 large-cell NECs (LCNECs, 27%) and 27 not otherwise specified NECs (nosNECs, 14.6%). The primary sites were the thorax (37%), gastroenteropancreatic sites (38%), unknown (15%) and other (9%). The mean Ki-67 index was 76% (range 20–100). Rb status was interpretable in 122 cases. Rb expression was lost in 74% of the cases: 84% of SCNEC vs. 60% and 63% of LCNEC and nosNEC, respectively (p = 0.016). Objective response was seen in 70% of SCNEC, 45% of LCNEC and 48% of nosNEC (p < 0.001) and in 62% of Rb-negative tumours vs. 46% of Rb-positive tumours (p = 0.3). There was no difference in median progression-free survival or overall survival (OS) as per Rb status. Age, NEC score and response to chemotherapy were the main factors associated with OS in our cohort. Conclusion: In our series, Rb status had no prognostic impact in PE-treated metastatic patients with NEC, whereas age, NEC score and response to chemotherapy were the main factors associated with OS Highlights: Neuroendocrine carcinomas are aggressive malignant diseases with a bad prognosis. Rb loss of expression might be a key prognostic/predictive parameter. Multicenter data confirm the NEC score as the only prognostic factor on OS. Rb status had no prognostic effect on OS or progression-free survival.